Geographical distribution of Enterobacterales with a carbapenemase IMP-6 phenotype and its association with antimicrobial use: An analysis using comprehensive national surveillance data on antimicrobial resistance - Hirabayashi, Aki (PLoS One, 2020)
Enterobacterales resistant to carbapenems, a class of last-resort antimicrobials, are ranked as an “urgent” and “critical” public health hazard by CDC and WHO. IMP-type carbapenemase-containing Enterobacterales are endemic in Japan, and bla(IMP-6) is one of the notable carbapenemase genes responsible for the resistance. The gene is plasmid-encoded and confers resistance to meropenem, but not to imipenem. Therefore, IMP-6-producing Enterobacterales isolates are occasionally overlooked in clinical laboratories and are referred to as ‘stealth-type’. Since previous reports in Japan were confined only to some geographical regions, their distribution across prefectures and the factors affecting the distribution remain unclear. Here, we revealed the dynamics of the geographical distribution of Enterobacterales with IMP-6 phenotype associated with antimicrobial use in Japan. We utilized comprehensive national surveillance data of all routine bacteriological test results from more than 1,400 hospitals in 2015 and 2016 to enumerate Escherichia coli and Klebsiella pneumoniae isolates with the antimicrobial susceptibility pattern (phenotype) characteristic of IMP-6 (imipenem susceptible, meropenem resistant), and to tabulate the frequency of isolates with the phenotype for each prefecture. Isolates were detected in approximately half of all prefectures, and combined analysis with the national data of antimicrobial usage revealed a statistically significant association between the frequency and usage of not carbapenems but third-generation cephalosporins (p = 0.006, logistic mixed-effect regression) and a weaker association between the frequency and usage of fluoroquinolones (p = 0.043). The usage of third-generation cephalosporins and fluoroquinolones may select the strains with the IMP-6 phenotype, and contribute to their occasional spread. We expect the findings will promote antimicrobial stewardship to reduce the spread of the notable carbapenemase gene.